A Man Living in the Wilderness Presents With a Unique Case of Erysipelothrix rhusiopathiae Causing Primary CNS Infection - Kevin Andrew Smith; Alejandra Méndez; Lindsey J. Reese (Case Reports in Infectious Diseases)
We report the first published case of Erysipelothrix rhusiopathiae causing subdural empyema. This 66-year-old male patient had relevant exposure history including living in a tent in the woods and having direct contact with wildlife. His main symptom which triggered his presentation was diplopia with exam findings consistent with a left partial oculomotor nerve palsy. Initial attempts at less invasive source control via burr holes alone failed. He was treated successfully with craniectomy and aqueous penicillin G with a duration of 6 weeks following surgery. CNS infection as the primary manifestation of Erysipelothrix rhusiopathiae has been reported in only one other case based on our review of the literature. This pathogen demonstrates an ability to manifest infection in many ways and remains susceptible to narrow spectrum beta-lactams.